Diaspora & hybridity - Kalra, Virinder S.; Kaur, Raminder; Hutnyk, John, 1961-; Sage eBooks (London : SAGE, 2005)
The authors offer a critical assessment of the key literature on diaspora & hybridity, & how these concepts relate to the issues of social change & the pursuit of equality.
Specialized.
Description based on print version record.
Includes bibliographical references, filmography and index.
Keywords: Ethnicity; Hybridity (Social sciences); Emigration and immigration -- Social aspects; Electronic books